Nb-FAR-1: A key developmental protein affects lipid droplet accumulation and cuticle formation in Nippostrongylus brasiliensis. - Wenmin Qi; Fei Shen; Chuyue Wang; Juan Wen; Xi Pan; Zhongying Zhao; Lihua Xiao; Yaoyu Feng; Dongjuan Yuan (PLoS Neglected Tropical Diseases)
Fatty acid and retinol binding proteins (FARs) are lipid-binding protein that may be associated with modulating nematode pathogenicity to their hosts. However, the functional mechanism of FARs remains elusive. We attempt to study the function of a certain FAR that may be important in the development of Nippostrongylus brasiliensis. Nb-FAR-1 was highly expressed throughout developmental stages by RNA-seq data and qPCR analyses, and Nb-FAR-1 was a secretory protein and abundant in the excretory-secretory products. Nb-FAR-1 could bind fatty acids and retinol. Fatty acid pattern of parasitic adults was more similar to rat intestine than to free-living L3s, indicating that N. brasiliensis may be dependent on the host to obtain fatty acids. Lentivirus-mediated RNAi was performed on L3s, resulting in a reduction in the expression of Nb-far-1 gene. Furthermore, these RNAi effects could be maintained in several generations. The offspring L3s in Nb-far-1 RNAi group had a reduction in lipid droplets within the subcuticle and the swelling of the perioral epidermis, accompanied with down-regulated expression of enzymes in amino acid and glycerolipid metabolism and glycometabolism for growth by RNA-seq data. Adults in Nb-far-1 RNAi group had the crumpled epidermis loosely attached to the basal membrane of body surface and the breakage of mouth epidermis, accompanied with a decrease in adult egg-shedding and an appearance of abnormal eggs. In vitro culture of eggs showed decreased efficiency of egg hatchability and larval development in the Nb-far-1 RNAi group. Transcriptomic analysis showed that interference with Nb-far-1 expression induced downregulated expression of major sperm protein and serpin for reproduction, and collagen for epidermis formation in adults, most of which were relatively high expression in adults but low expression in L3s in the WT group. Thus, Nb-FAR-1 may affect the reproduction, growth, and development of N. brasiliensis by regulating the level of lipids.